Демонстрация силы: роман / Владимир Шитов - Шитов Владимир Кузьмич (АСТ, 2002)
Экземпляры: ф.22 (20181026) / Инвентарный номер: 58728 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: Ш 64 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-44